A multi-fuel pathway explorer tool for evaluating sustainable alternative fuels for the maritime sector - Reiter , Jana; Hoefer, Christoph; Pfleger, Jasmin; Gruber-Glatzl, Wolfgang (International Journal of Sustainable Energy Planning and Management, 2026)
In the maritime sector, sustainable alternative fuels derived from biological and non-biological origin such as hydrogen, ammonia, and methanol show high potential for novel propulsion technologies such as solid oxide fuel cells. Since transitioning to new fuels may require high investments, decision-makers and local municipalities need a systematic approach to identify the most relevant fuel pathways for their prerequisites. However, a modelling approach including fuel production, transport, demand, time-resolved supply rates for testing and comparing sustainable alternative fuels is still lacking. Here, a Python library called multi-fuel pathway explorer (MFPE) was developed, for fuel-cell applications in the maritime sector. The library offers the possibility of rapid screening and modelling of high-potential pathways depending on the constituents of the target port environment, allowing for in-depth evaluation of technical details compared to commonly applied life-cycle assessment (LCA) or techno-economical assessment (TEA) tools. For demonstration, a case study was set up at the port of Rotterdam to evaluate fuel pathways by calculation of selected key performance indicators (KPIs). Results demonstrate that the model is applicable on complex multi-fuel systems to compare fuel pathways, identify system-level bottlenecks, and analyse time-resolved dependencies between fuel demand and supply along the pathway.